Dampak Revolusi Energi Amerika Serikat Terhadap Perekonomian Arab Saudi - Zabadi, Fairuz (SIYAR Journal, 2021)
The relationship between the United States and Saudi Arabia originated largely from oil trade. Meanwhile, in 2014 to 2017 the United States energy revolution, that make United States as the world most large oil producer, became one of the causes of the number of oil imports as well as the US oil dependency from Saudi Arabia to decline. This research is trying to find out the impact of the United States energy revolution on the economy of Saudi Arabia. This research uses descriptive qualitative method using secondary data. By using documentation collection data technic, the research also using online data to enrich the data. This study uses the concept of interdependence in the economic impact of the United States Energy Revolution on Saudi Arabia. This research found the fact that the United States made Saudi Arabia suffer losses due to reduced income and this made Saudi Arabia want to diversify their economies.